Early inhibition of IL-1β expression by IFN-γ is mediated by impaired binding of NF-[kappa]B to the IL-1β promoter but is independent of nitric oxide - Eigenbrod, Tatjana; Bode, Konrad A.; Dalpke, Alexander (The journal of immunology, 2013)
The significance of bacterial RNA recognition for initiating innate immune responses against invading pathogens has only recently started to be elucidated. Bacterial RNA is an important trigger of inflammasome activation, resulting in caspase-1-dependent cleavage of pro-IL-1β into the active form. It was reported previously that prolonged treatment with IFN-γ can inhibit IL-1β production at the level of both transcription and Nlrp3 inflammasome activation in an NO-dependent manner. As a result of the delayed kinetics of NO generation after IFN-γ stimulation, these effects were only observed at later time points. We report that IFN-γ suppressed bacterial RNA and LPS induced IL-1β transcription in primary murine macrophages and dendritic cells by an additional, very rapid mechanism that was independent of NO. Costimulation with IFN-γ selectively attenuated binding of NF-κB p65 to the IL-1β promoter, thus representing a novel mechanism of IL-1β inhibition by IFN-γ. Transcriptional silencing was specific for IL-1β because expression of other proinflammatory cytokines, such as TNF, IL-6, and IL-12p40, was not affected. Furthermore, by suppressing IL-1β production, IFN-γ impaired differentiation of Th17 cells and production of neutrophil chemotactic factor CXCL1 in vitro. The findings provide evidence for a rapid immune-modulating effect of IFN-γ independent of NO.
Im Titel ist "kappa" als griechischer Buchstabe dargestellt
Gesehen am 12.01.2021